Interrupted Aortic Arch in an Adult with Polycystic Kidney Disease - Ayşe Şeker Koçkara; Mansur Kayataş; Can Huzmeli; Ferhan Candan; Cesur Gümüş (Case Reports in Medicine)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary kidney disease and is responsible for 8–10% of patients with end-stage renal failure. The major extrarenal complications of ADPKD are cardiovascular abnormalities. Interrupted aortic arch (IAA) is a lethal congenital cardiac abnormality seen with a frequency of 3/1000000 births and is defined as a segment of the arcus aorta being atresic. In the literature, there are no any reports showing that polycystic kidney disease and interrupted aortic arch occur together. In this study, we present a rare case in which the patient has polycystic kidney disease and IAA together and discuss whether IAA is a complication of ADPKD.